Sistemática dos porcos-espinhos do gênero Coendou Lacépède, 1799 (Rodentia: Erethizontidae) - Lima, Fernando Heberson Menezes (2023)
The new world porcupines are medium sized rodents of the Erethizontidae family, which is divided into three genera, Chaetomys, Erethizon and Coendou, with and 18 species. Chaetomys and Erethizon are monospecific and almost all species are in the genus Coendou. The porcupines are hard to record and capture due their arboreal, nocturnal, and florivorous habits, which restricts the amount of information available in scientific collections and genetic samples. In this way, information on morphological variation, distribution and biology of porcupines are messy and incomplete, mainly in Amazonian species. Consequently, it lacks quality samples as identification references of the porcupine species, resulting in a chaotic taxonomical history. Traditionally, the genus Coendou is divided in two subgenera, Coendou and Sphiggurus, although, there is no concordance about the diagnostic characters. Previous phylogenetic analyses and taxonomic assessments described new species and suggested the diagnostic characters of both subgenera are homoplasies. As a result, the interpretation that Coendou and Sphiggurus are, respectively, polyphyletic, and paraphyletic. Here, through an integrative systematic approach, we described a third subgenus, named Caaporamys, and new diagnostic characters for the subgeneric classification. Therefore, the subgeneric classification of the genus Coendou is solved. Additionally, the species of Coendou prehensilis complex were delimited: Coendou prehensilis, Coendou longicaudatus and Coendou baturitensis. The species are allopatric and can be identified through quills and cranial traits. Finally, Coendou roosmalenorum has its phylogenetics position and distribution investigated, confirming its position as a Caaporamys species distributed in Madeira Province.